Understanding and Managing International Product Launch: A Comparison between Developed and Emerging Markets - Lee, Yikuan; Lin, Bou-Wen; Wong, Yim-Yu; Calantone, Roger J. (The Journal of product innovation management, 2011)
With the developed market becoming increasingly saturated, companies have turned to the rapidly growing emerging market. To compete effectively in the global marketplace, firms need to develop global market competences, such as effective product launch. Although considerable efforts have been devoted to identifying principles of effective new product launch, most of the literature focuses on a single country (i.e., the domestic market) and provides little direct cross‐national comparison. The objective of this study is to provide a better understanding of the patterns of effective product launch in the developed and emerging markets. Drawing from the contingency perceptive, the authors propose a conceptual model that emphasizes the central role of tactical launch decisions and the need to cope with the internal and external constraints for maximum new product performance. The research model is tested on 284 new products launched in the United States and 97 in Taiwan. Although prior literature suggested certain elements of global product launch may be standardized for purposes of efficiencies, the empirical data from this study suggests that global launch requires some degree of customization. The insights of the findings reveal that while some tactical launch decisions are effective for both emerging and mature markets, some are detrimental to each other. For example, customer education preannouncement and promotion discount pricing strategy enhance new product performance and preemption preannouncement strategy upset consumers for both the Taiwan and U.S. market. However, there are some cross‐national differences. Emotional advertising strategy is generally appreciated in the U.S. market but not in the Taiwan market. For management practice, the findings suggest the distinct patterns of effective product launch for the emerging and mature market using the United States and Taiwan as examples.